Certification of applicators - Buffington, E. J., author; McDonald, S. K., author; Colorado Environmental Pesticide Education Program, publisher (Colorado State University. Libraries, 2006)
This fact sheet describes the differences between private and commercial pesticide applicators and lists the types of commercial applicators.
CEPEP 10/01, reviewed 5/04, updated 6/06.
PLEASE NOTE: This fact sheet is a historical document and some information may not reflect current federal and state laws and regulations and best practices.
Keywords: Pesticide applicators (Persons); Pesticides -- Handling